Turning China's money reserves into capital - Miriam L. Campanella (European Centre for International Political Economy (ECIPE), 2015)
Some economies in East Asia have built up large amounts of foreign exchange reserves in the past decades. Holding large amounts of reserves helped these economies to stabilize their macro economy and exchange rates under periods of market stress and rapid shifts in relative economic size. Generally, it has been a strategy to provide a defence against external shocks with damaging consequences for exports. Rules aimed at limiting foreign reserves, in order to prevent currency manipulation, have been discussed over a long period of time. Yet there are to date no rules that come with effective disciplines - and it is unlikely that such rules can be agreed multilaterally, at least for the foreseeable future. What measures has China adopted to cope with these challenges? (...)
Keywords: 330; Währungsreserven; China